(untitled) (European Journal of Pure and Applied Mathematics, 2023)
This study introduces the concept of Gamma-ideals and Gamma-submonoids of Gamma-monoids and investigates their relationships with the existing Gamma-order-ideals. Moreover, quotient of Gamma-monoids and isomorphism theorems via Gamma-submonoids are proved.